Preparation method of superfine sand concrete
The ultra-fine sand concrete is solved by combining large-particle nickel-iron slag with extra-fine sand and specific treatment of small-particle nickel-iron slag sand to form a mixture with high specific surface area, and using pre-wet gauze in the concrete, the ultra-fine sand concrete is solved by combining large-particle nickel-iron slag sand and specific treatment of small-particle nickel-iron slag sand to form a mixture with high specific surface The problems of high shrinkage and poor stability of nickel-iron slag sand significantly improve the mechanical properties of concrete.
Patent Information
- Application Number
- CN202411779283.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-05
- Publication Date
- 2025-02-21
AI Technical Summary
Extrafine sand concrete is difficult to be widely used in construction projects due to its high shrinkage and poor stability when nickel-iron slag sand replaces natural sand.
By combining large-particle nickel-iron slag with extra fine sand, and processing small-particle nickel-iron slag sand, including grinding powder, tartaric acid solution soaking, pH adjustment, carbonization curing and adding carbonate grinding powder, the ratio is formed A mixture with a surface area of >300 m2/kg and a prewet gauze was flatly laid in concrete to improve crack resistance.
It effectively reduces the shrinkage of extra-fine sand concrete, improves the stability of nickel-iron slag sand, significantly improves the flexural strength and compressive strength of concrete, and reduces the drying shrinkage ratio.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of building materials, and in particular to a method for preparing ultra-fine sand concrete. Background Art
[0002] River sand, as a natural resource, is an important raw material for preparing concrete and mortar. However, with the continuous expansion of infrastructure construction, most parts of my country, especially Jiangsu, are facing a shortage of natural sand resources and a decline in the quality of natural sand. And because river sand mining can easily cause serious damage to the riverbed and the surrounding natural environment, some rivers have banned or restricted the mining of river sand. Under the dual influence of rigid market demand and increasingly scarce resources, the price of river sand continues to rise.
[0003] At present, my country has abundant reserves of ultra-fine sand, which is easy to mine and transport. The scientific and rational use of ultra-fine sand has significant social and economic benefits in saving energy, reducing project costs, and shortening construction periods, and is in line with the principle of "adapting measures to local conditions and using local materials". Ultra-fine sand has fine particles, large total surface area, large porosity, and large water demand, which leads to an increase in the water-cement ratio of ultra-fine sand concrete, a large amount of total cementitious materials, and more serious shrinkage cracking.
[0004] At the same time, my country discharges a large amount of industrial waste slag every year due to industrial production, such as iron slag, steel slag, red mud, nickel-iron slag, etc. If ultra-fine sand, nickel-iron slag composite, etc. are used to replace natural sand to prepare concrete, it can solve the problem of shortage of natural sand on the one hand, and also solve the problem of indiscriminate discharge and dumping on the other hand.
[0005] The invention provides concrete prepared by using ultra-fine sand and nickel-iron slag sand, aiming to solve the high shrinkage problem of ultra-fine sand concrete and the poor stability problem when nickel-iron slag sand is used instead of natural sand. Summary of the invention
[0006] Purpose of the invention: In view of the problems existing in the prior art, the present invention provides a method for preparing ultra-fine sand concrete, which comprises the steps of compounding large-size nickel-iron slag with ultra-fine sand; grinding small-size nickel-iron slag sand, soaking it in tartaric acid solution, adjusting the pH value with sodium hydroxide, carbonizing and curing it, and adding carbonate to grind it to a specific surface area of 300m 2 / kg; measures such as laying a layer of pre-wetted cotton gauze in the concrete every 3 to 5 cm have solved the high shrinkage problem of ultra-fine sand concrete and the poor stability problem when nickel-iron slag sand is used instead of natural sand.
[0007] Technical solution: A method for preparing ultra-fine sand concrete, comprising the following steps: 1) Surface treatment of ultra-fine sand: spray sodium lignin sulfonate solution on the surface of ultra-fine sand and dry it naturally until there is no visible water on the surface; the fineness modulus of the ultra-fine sand is 0.3~1.0; 2) Screening of nickel-iron slag sand: Screen the nickel-iron slag sand into nickel-iron slag sand with a particle size of more than 1 mm and nickel-iron slag sand with a particle size of ≤1 mm; 3) Preparation of sand conforming to the graded zone II: Adding nickel-iron slag sand with a particle size of >1 mm to the ultra-fine sand treated in step 1) to obtain composite sand, so that the particle gradation of the composite sand conforms to the graded zone II sand; 4) Treatment of small-size nickel-iron slag sand: grind the nickel-iron slag sand with a particle size of ≤1mm into powder, soak it in tartaric acid solution, and then adjust the pH value of the solution to 9-10; take out the soaked nickel-iron slag powder, dry it naturally until the moisture content is 1-10%, and perform carbonization curing; finally, mix the nickel-iron slag powder after carbonization curing with carbonate, and grind it to a specific surface area of >300m 2 / kg; 5) Concrete molding and pouring: weigh the cementitious material, gravel, composite sand from step 3), the mixture of nickel-iron slag powder and carbonate from step 4), water, and water reducing agent in proportion, mix them evenly, and pour them into a concrete mold; wherein, lay a layer of pre-wetted cotton gauze in the concrete every 3-5 cm; 6) Concrete curing: The concrete poured in step 5) is cured with saturated lime water for more than 7 days to obtain extra fine sand concrete.
[0008] Furthermore, in step 1), the mass fraction of the sodium lignin sulfonate solution is 1.0-1.5%.
[0009] Preferably, in step 4), the specific conditions for soaking are: soaking in a tartaric acid solution with a concentration of 0.01-0.3 mol / L for 2-3 hours.
[0010] Furthermore, in step 4), the specific conditions of the carbonization curing are: CO2 mass fraction is 40-100%, and the curing time is 6-24h.
[0011] Furthermore, in step 4), the mass ratio of the ferronickel slag powder to the carbonate in the mixture of ferronickel slag powder and carbonate after carbonization curing is 85-95%:5-15%.
[0012] Furthermore, in step 5), the particle size of the stones is less than 10 mm.
[0013] Furthermore, in step 5), the mass of the mixture of nickel-iron slag powder and carbonate after treatment accounts for 1-5% of the mass of the cementitious material.
[0014] Furthermore, in step 5), the specific treatment method of the pre-wetted cotton gauze is: soaking the cotton gauze in a water glass solution with a modulus of 1.5-3.5 diluted 5-20 times, taking it out, filtering and centrifuging it, so that the water absorption rate of the cotton gauze is maintained at 10-30%.
[0015] Beneficial effects: Compared with the prior art, the present invention has the following specific beneficial effects: (1) Nickel-iron slag sand has high content of magnesium and iron elements and large elastic modulus. When mixed with ultra-fine sand to prepare composite sand, it can partially offset the problem of large shrinkage of ultra-fine sand concrete. At the same time, nickel-iron slag has a smooth surface and a spherical shape. It has good fluidity and small water demand, which can partially offset the problem of large water demand of ultra-fine sand concrete.
[0016] (2) Through screening, nickel-iron slag sand with and without stability problems are separated to reduce the stability problem of concrete: the nickel-iron slag with large particle size and good stability is directly mixed with ultra-fine sand; the nickel-iron slag with small particle size and poor stability is treated: by using polyhydroxycarboxylic acid - tartaric acid to decompose the small-particle nickel-iron slag with high activity and poor stability (the product is orthosilicic acid, salt carrying magnesium ions, calcium ions, and iron ions), further adjusting the pH value, air drying and carbonization, it can be further converted into a mixture mainly composed of magnesium carbonate and a small amount of calcium carbonate and sodium silicate. With the assistance of carbonates, this mixture, when in contact with water and the hydration products calcium hydroxide and hydrated calcium aluminate in cement, can form expansive hydrated magnesium carbonate, calcium vanadate, etc., which can compensate for the shrinkage caused by the ultra-fine sand concrete. At the same time, the hydrated magnesium carbonate and calcium vanadate carry a large amount of bound water, which can consume the excess water brought to the concrete by the fine particles of ultra-fine sand.
[0017] (3) The use of cotton gauze in the paving of ultra-fine sand concrete can improve the crack resistance of ultra-fine sand concrete. In addition, cotton gauze can absorb water and absorb the excess water gathered around the ultra-fine sand particles after hardening, and transfer the water to the places where the cement is hydrated and lacks water inside the concrete. At the same time, when there is a lack of water inside the concrete, cotton gauze, as a continuous fiber, can replenish water from the external wet curing environment to the areas around the concrete that lack water and unhydrated cement particles, thereby playing a role in replenishing water and improving the strength of the concrete.
[0018] (4) By spraying sodium lignin sulfonate solution on the surface of ultra-fine sand, the agglomeration phenomenon caused by the small size of ultra-fine sand particles can be solved, and the dispersion uniformity of ultra-fine sand in concrete can be improved. At the same time, lignin sulfonate solution is sprayed on the surface of fine aggregate as a surfactant, which can affect the crystallization state of calcium hydroxide, the cement hydration product, and reduce the crystallization of large-scale calcium hydroxide crystals near the fine aggregate, which can improve the interfacial bonding strength between fine aggregate and cement paste. DETAILED DESCRIPTION
[0019] The present invention is described in detail below in conjunction with the embodiments. In order to more clearly understand the embodiments of the present invention, the concrete mix ratios of the comparative example and embodiments 1 to 4 are listed in detail in Table 1.
[0020] Embodiment 1: A method for preparing ultra-fine sand concrete comprises the following steps: Surface treatment of ultra-fine sand: spray a layer of sodium lignin sulfonate solution with a mass fraction of 1.5% on the surface of ultra-fine sand with a fineness modulus of 0.3, and dry it naturally until there is no visible water on the surface; Nickel iron slag sand screening: the nickel iron slag sand is screened into nickel iron slag sand with a particle size of more than 1mm and nickel iron slag sand with a particle size of ≤1mm; 3) Preparation of sand conforming to the gradation zone II: Adding nickel-iron slag sand with a particle size of >1 mm to the ultra-fine sand treated in step 1) to obtain composite sand, so that the particle gradation of the composite sand conforms to the gradation zone II, and the mass ratio of ultra-fine sand to nickel-iron slag is 25:75; 4) Treatment of small-size nickel-iron slag sand: grind the nickel-iron slag sand ≤1mm into powder and soak it in 0.01mol / L tartaric acid solution for 3 hours; then use sodium hydroxide to adjust the pH value of the solution to 9, take out the nickel-iron slag powder and dry it naturally until the moisture content is 10%, then use 40% concentration of CO2 carbonization and curing for 24 hours, then grind the 95% carbonized nickel-iron slag powder with 5% sodium carbonate to a specific surface area of 320m 2 / kg; 5) Concrete molding and pouring: according to Table 1, weigh the cementitious materials (cement, mineral powder, fly ash), the mixture of treated nickel-iron slag powder and carbonate, ultra-fine sand, nickel-iron slag sand, gravel (particle size less than 10mm), water, and water reducer, mix them evenly, and pour them into the concrete mold; wherein, spread a layer of pre-wetted cotton gauze in the concrete every 5cm; pre-wetted cotton gauze means that the cotton gauze is soaked in a water glass solution with a modulus of 3.5 diluted 20 times as the pre-wet solution, then taken out, filtered, and centrifuged to keep its water absorption rate at 10%; 6) Concrete curing: The concrete is cured with saturated lime water for 14 days to obtain extra fine sand concrete.
[0021] Embodiment 2: A method for preparing ultra-fine sand concrete comprises the following steps: Surface treatment of ultra-fine sand: spray a layer of 1.0% sodium lignin sulfonate solution on the surface of ultra-fine sand with a fineness modulus of 1.0, and dry it naturally until there is no visible water on the surface; Nickel iron slag sand screening: the nickel iron slag sand is screened into nickel iron slag sand with a particle size of more than 1mm and nickel iron slag sand with a particle size of ≤1mm; Preparation of sand conforming to the gradation zone II: adding nickel-iron slag sand with a particle size of >1 mm to the ultra-fine sand treated in step 1) to obtain composite sand, so that the particle gradation of the composite sand conforms to the gradation of the sand in zone II, and the mass ratio of ultra-fine sand to nickel-iron slag sand is 20:80; 4) Treatment of small-size nickel-iron slag sand: grind the nickel-iron slag sand ≤1mm into powder, soak it in 0.3mol / L tartaric acid solution for 2 hours; then use sodium hydroxide to adjust the pH value of the solution to 9, take out the nickel-iron slag powder and dry it naturally until the moisture content is 1%, then use 50% concentration of CO2 for carbonization and curing for 12 hours, then add 15% carbonate and grind it to a specific surface area of 350m 2 / kg; 5) Concrete molding and pouring: according to Table 1, weigh the cementitious materials (cement, mineral powder, fly ash), the mixture of treated nickel-iron slag powder and carbonate, ultra-fine sand, nickel-iron slag sand, gravel (particle size less than 10mm), water, and water reducer, mix them evenly, and pour them into the concrete mold; wherein, spread a layer of pre-wetted cotton gauze in the concrete every 3cm; pre-wetted cotton gauze means that the cotton gauze is soaked in a water glass solution with a modulus of 1.5 diluted 5 times as the pre-wet solution, then taken out, filtered, and centrifuged to keep its water absorption rate at 30%; 6) Concrete curing: The concrete is cured with saturated lime water for 28 days to obtain extra fine sand concrete.
[0022] Embodiment 3: A method for preparing ultra-fine sand concrete comprises the following steps: Surface treatment of ultra-fine sand: spray a layer of sodium lignin sulfonate solution with a mass fraction of 1.2% on the surface of ultra-fine sand with a fineness modulus of 0.5, and dry it naturally until there is no visible water on the surface; Nickel iron slag sand screening: the nickel iron slag sand is screened into nickel iron slag sand with a particle size of more than 1mm and nickel iron slag sand with a particle size of ≤1mm; 3) Preparation of sand conforming to the graded zone II: Adding nickel-iron slag sand with a particle size of >1 mm to the ultra-fine sand treated in step 1) to obtain composite sand, so that the particle gradation of the composite sand conforms to the graded zone II sand, and the mass ratio of ultra-fine sand to nickel-iron slag is 30:70; 4) Treatment of small-size nickel-iron slag sand: grind the nickel-iron slag sand ≤1mm into powder, soak it in 0.1mol / L tartaric acid solution for 2 hours; then use sodium hydroxide to adjust the pH value of the solution to 10, take out the nickel-iron slag powder and dry it naturally to a moisture content of 5%, then use 100% concentration of CO2 for carbonization and curing for 6 hours, then add 10% carbonate and grind it to a specific surface area of 330m 2 / kg; 5) Concrete forming and pouring: according to Table 1, weigh the cementitious materials (cement, mineral powder, fly ash), the mixture of treated nickel-iron slag powder and carbonate, ultra-fine sand, nickel-iron slag sand, gravel (particle size less than 10mm), water, and water reducer, mix them evenly, and pour them into the concrete mold; wherein, spread a layer of pre-wetted cotton gauze in the concrete every 4cm; pre-wetted cotton gauze means that the cotton gauze is soaked in a water glass solution with a modulus of 2.0 diluted 10 times as the pre-wet solution, then taken out, filtered, and centrifuged to keep its water absorption rate at 20%; 6) Concrete curing: The concrete is cured with saturated lime water for 8 days to obtain extra fine sand concrete.
[0023] Embodiment 4: A method for preparing ultra-fine sand concrete comprises the following steps: Surface treatment of ultra-fine sand: spray a layer of sodium lignin sulfonate solution with a mass fraction of 1.3% on the surface of ultra-fine sand with a fineness modulus of 0.7, and dry it naturally until there is no visible water on the surface; Nickel iron slag sand screening: the nickel iron slag sand is screened into nickel iron slag sand with a particle size of more than 1mm and nickel iron slag sand with a particle size of ≤1mm; 3) Preparation of sand conforming to the gradation zone II: Add nickel-iron slag sand with a particle size of >1 mm to the ultra-fine sand in step 1) to obtain composite sand, so that the particle gradation of the composite sand conforms to the gradation of the sand in zone II, and the mass ratio of ultra-fine sand to nickel-iron slag sand is 25:75; 4) Treatment of small-size sand nickel-iron slag: grind the nickel-iron slag sand ≤1mm into powder, soak it in 0.15mol / L tartaric acid solution for 2 hours; then use sodium hydroxide to adjust the pH value of the solution to 9, take out the nickel-iron slag powder and dry it naturally to a moisture content of 8%, then use 50% concentration of CO2 for carbonization and curing for 12 hours, then add 8% carbonate and grind it to a specific surface area of 330m 2 / kg; 5) Concrete forming and pouring: according to Table 1, weigh the cementitious materials (cement, mineral powder, fly ash), the mixture of treated nickel-iron slag powder and carbonate, ultra-fine sand, nickel-iron slag sand, gravel (particle size less than 10mm), water, and water reducer, mix them evenly, and pour them into the concrete mold; wherein, spread a layer of pre-wetted cotton gauze in the concrete every 3cm; pre-wetted cotton gauze means that the cotton gauze is soaked in a water glass solution with a modulus of 2.0 diluted 10 times as the pre-wet solution, then taken out, filtered, and centrifuged to keep its water absorption rate at 25%; 6) Concrete curing: The concrete is cured with saturated lime water for 14 days to obtain extra fine sand concrete.
[0024]
[0025] Performance Testing In order to facilitate understanding of the technical measures of the present invention, the present invention selects specific nickel-iron slag sand with a fineness modulus of 3.68.
[0026] The reference concrete is used as a comparative example. The reference concrete mix ratio is as follows: 260kg cement, 65kg mineral powder, 50kg fly ash, 750kg river sand, 1100kg coarse aggregate, 170kg water, and 8kg water reducer, see Table 1. It should be noted that the mixture in step 4) of Examples 1-4 is used to partially replace the fly ash in the reference concrete mix ratio; the ultra-fine sand and nickel-iron slag sand in Examples 1-4 are used to completely replace the river sand in the reference concrete mix ratio. In order to facilitate the comparison of the mechanical properties of the 28-day sample test, the samples in Examples 1 to 4 with a wet curing time of less than 28 days are continued to be cured in water at 22±3℃ for 28 days. The curing conditions of the mechanical properties test samples of the comparative example are 28 days in water at 22±3℃, and all drying shrinkage samples are not wet cured.
[0027] Table 2 shows the performance evaluation indexes of the present invention. The performance evaluation of Examples 1-4 and the comparative example is performed with reference to the "Test Method for Stability of Cement Autoclave" (GBT750-1992), "Standard Ordinary Concrete Mechanical Test Method" (GB / T50081-2002) and the standard "Standard for Test Methods for Long-term Performance and Durability of Ordinary Concrete" (GB / T 50082-2009).
[0028]
[0029] As shown in Table 1, the stability of the ultra-fine sand concrete prepared by the present invention is qualified, and no cracking and obvious expansion occur under the pressure steaming condition, eliminating the hidden danger of volume stability of nickel-iron slag sand concrete. At the same time, the slump of the ultra-fine sand concrete prepared by the present invention is basically the same as that of pure natural sand concrete, and the flexural strength of the concrete can be greatly improved, and the compressive strength is also improved. More specifically, the shrinkage of the ultra-fine sand concrete prepared by the present invention is lower than the drying shrinkage of the concrete prepared with natural river sand.
[0030] The above embodiments are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with the technology to understand the content of the present invention and implement it accordingly, and they cannot be used to limit the protection scope of the present invention. Any equivalent transformation or modification made according to the spirit of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing ultra-fine sand concrete, characterized in that: The following steps are involved: 1) Surface treatment of ultra-fine sand: spray sodium lignin sulfonate solution on the surface of ultra-fine sand and dry it naturally until there is no visible water on the surface; the fineness modulus of the ultra-fine sand is 0.3~1.0; 2) Screening of nickel-iron slag sand: Screen the nickel-iron slag sand into nickel-iron slag sand with a particle size of more than 1 mm and nickel-iron slag sand with a particle size of ≤1 mm; 3) Preparation of sand conforming to the graded zone II: Adding nickel-iron slag sand with a particle size of >1 mm to the ultra-fine sand treated in step 1) to obtain composite sand, so that the particle gradation of the composite sand conforms to the graded zone II sand; 4) Treatment of small-size nickel-iron slag sand: grind the nickel-iron slag sand with a particle size of ≤1mm into powder, soak it in tartaric acid solution, and then adjust the pH value of the solution to 9-10; take out the soaked nickel-iron slag powder, dry it naturally until the moisture content is 1-10%, and perform carbonization curing; finally, mix the nickel-iron slag powder after carbonization curing with carbonate, and grind it to a specific surface area of >300m 2 / kg; 5) Concrete molding and pouring: weigh the cementitious material, gravel, composite sand from step 3), the mixture of nickel-iron slag powder and carbonate from step 4), water, and water reducing agent in proportion, mix them evenly, and pour them into a concrete mold; wherein, lay a layer of pre-wetted cotton gauze in the concrete every 3-5 cm; 6) Concrete curing: The concrete poured in step 5) is cured with saturated lime water for more than 7 days to obtain extra fine sand concrete.
2. The method for preparing ultra-fine sand concrete according to claim 1, characterized in that: In step 1), the mass fraction of the sodium lignin sulfonate solution is 1.0-1.5%.
3. The method for preparing ultra-fine sand concrete according to claim 1, characterized in that: In step 4), the specific conditions of the soaking are: soaking in a tartaric acid solution with a concentration of 0.01-0.3 mol / L for 2-3 hours.
4. The method for preparing ultra-fine sand concrete according to claim 1, characterized in that: In step 4), the specific conditions of the carbonization curing are: CO2 mass fraction is 40-100%, and the curing time is 6-24h.
5. The method for preparing ultra-fine sand concrete according to claim 1, characterized in that: In step 4), the mass ratio of the ferronickel slag powder to the carbonate in the mixture of ferronickel slag powder and carbonate after carbonization curing is 85-95%:5-15%.
6. The method for preparing ultra-fine sand concrete according to claim 1, characterized in that: In step 5), the particle size of the stones is less than 10 mm.
7. The method for preparing ultra-fine sand concrete according to claim 1, characterized in that: In step 5), the mass of the mixture of nickel-iron slag powder and carbonate after treatment accounts for 1-5% of the mass of the cementitious material.
8. The method for preparing ultra-fine sand concrete according to claim 1, characterized in that: In step 5), the specific treatment method of the pre-wetted cotton gauze is: soak the cotton gauze in a water glass solution with a modulus of 1.5-3.5 diluted 5-20 times, take it out, filter and centrifuge it, so that the water absorption rate of the cotton gauze is maintained at 10-30%.